2019
DOI: 10.1186/s13148-019-0617-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of epigenetic changes during hematopoietic differentiation of induced pluripotent stem cells

Abstract: BackgroundDifferentiation of induced pluripotent stem cells (iPSCs) toward hematopoietic progenitor cells (HPCs) raises high hopes for disease modeling, drug screening, and cellular therapy. Various differentiation protocols have been established to generate iPSC-derived HPCs (iHPCs) that resemble their primary counterparts in morphology and immunophenotype, whereas a systematic epigenetic comparison was yet elusive.ResultsIn this study, we compared genome-wide DNA methylation (DNAm) patterns of iHPCs with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
(76 reference statements)
2
12
0
Order By: Relevance
“…3g). DNAm profiles of wildtype iHPCs indicated multilineage differentiation, similar to previously published iHPC profiles (Cypris et al, 2019; Nishizawa et al, 2016). Despite the impact of exon 19 -/- and exon 23 -/- on de novo DNAm, estimates for cellular composition were similar between wildtype and knockout iHPCs.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…3g). DNAm profiles of wildtype iHPCs indicated multilineage differentiation, similar to previously published iHPC profiles (Cypris et al, 2019; Nishizawa et al, 2016). Despite the impact of exon 19 -/- and exon 23 -/- on de novo DNAm, estimates for cellular composition were similar between wildtype and knockout iHPCs.…”
Section: Resultssupporting
confidence: 87%
“…CpG sites associated with promotor regions are shown without transparency. (g) A deconvolution algorithm (Houseman et al ., 2012) was used to estimate the composition of different mature hematopoietic cell types based on the DNAm profiles of our iHPCs, those of Nishizawa et al (Nishizawa et al ., 2016) and of our previously published iHPC data (Cypris et al ., 2019). h) Gene expression changes compared between WT iHPCs and exon 19 -/- or exon 23 -/- iHPCs depicted as log 2 fold change against the mean of normalized counts of all samples regarding sequencing depth (=base mean).…”
Section: Resultsmentioning
confidence: 77%
“…A recent report demonstrated that directed hematopoietic differentiation of hiPSCs using morphogens yields CD45 + cells that are epigenetically distinct from wild type human HSCs, when comparing their genome-wide DNA methylation patterns. Additionally, prolonged co-culture with stromal cells did not induce further epigenetic maturation of these iPSC-derived cells [150]. Taken together, with current differentiation protocols, iPSC-derived hematopoietic stem/progenitors seem to be both functionally and epigenetically immature, which brings into question their suitability for clinical application.…”
Section: Fig (3) Multiplexed Transcriptional Gene Activation or Repression By Crispr-dcas9 A)mentioning
confidence: 93%
“…It is well established that epigenetics contributes significantly to the developmental fate of cells and tissues [ 8 ]. For instance, epigenetic mechanisms contribute to the differentiation of hematopoietic stem cells from bone marrow [ 12 , 13 ]. Importantly, DNA methylation appears to play a crucial role at specific stages along the separation of blood cell lineages (myeloid, lymphoid) and contributes to the establishment and functionality of the final differentiated cell type [ 14 ].…”
Section: Introductionmentioning
confidence: 99%